The Phenomenon of Social Deviation in School-Age Adolescents: A Sociological Perspective - Pangesti, Suci Annisa; Dora, Nuriza (Ilomata International Journal of Social Science, 2025)
This study aims to explore the phenomenon of social deviance among school-age adolescents from a sociological perspective. Social deviance refers to behavior or actions that deviate from social norms or standards accepted in society. This study uses a qualitative approach with a case study method to understand various forms of social deviance that occur among adolescents, such as substance abuse, criminal behavior, and other actions that are considered to violate norms. Data were collected through in-depth interviews with adolescents, parents, and educators, as well as field observations in schools and communities. The findings of the study indicate that factors such as peer pressure, lack of parental supervision, and personal dissatisfaction play a significant role in influencing deviant behavior. In addition, social structures and cultural norms also contribute to the community's understanding and response to such deviance. This study underlines the importance of interventions involving various parties, including families, schools, and communities, to address social deviance and support positive adolescent development. The results of this study are expected to provide valuable insights for policy makers, educators, and social practitioners in designing strategies for preventing and handling social deviance among adolescents.